Plant Community Structure and Species Diversity in Ranibari Forest, Kathmandu - Maharjan, S. R.; Bhuju, D. R.; Khadka, C. (Nepal Journal of Science and Technology, 2007)
The growth of urban population in Kathmandu has resulted in increased degradation of its forests and consequently increased recreational pressure on them. Ranibari forest (area 7.6 ha), situated at the north west region of Kathmandu valley represents a typical such forest in Kathmandu. Quantitative study was carried to assess the structural dimensions and analyze community structure of the forest. Samplings were done in 26 large quadrats (size: 25mx25m) for canopy stratum, 52 medium plots (size: 5mx5m) for understory stratum and 130 small plots (size: 1mx1m) for the study of ground vegetation. The forest was floristically rich with a total of 108 species belonging to 58 families and 92 genera. The canopy stratum was predominated by dense clumps of bamboos and tree species of regional flora such as Zizyphus incurva, Stranvaesia nussia, Persea duthiei, Engelhardtia spicata, Celtis australis, and Schima wallichii. The shrub vegetation was relatively poor, dominated by invasive alien Lantana camara and associated with Sarcococca coriacea and Ligustrum confusum. The low densities of seedling and sapling indicated weak regeneration in the forest. Human activities such as plantations have modified the natural habitat of the forest and brought patchiness. The trampling disturbance on the ground was found detrimental to the growth of seedlings and vegetation coverage though it added some herb species richness. Nepal Journal of Science and Technology Vol. 7, 2006